2011
DOI: 10.1093/ndt/gfr456
|View full text |Cite
|
Sign up to set email alerts
|

The German Chronic Kidney Disease (GCKD) study: design and methods

Abstract: The GCKD study will establish one of the largest cohorts to date of CKD patients not requiring renal replacement therapy. Similarities in its design with other observational CKD studies, including cohorts that have already been established in the USA and Japan, will allow comparative and joint analyses to identify important ethnic and geographic differences and to enhance opportunities for identification of relevant risk factors and markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 30 publications
2
159
0
1
Order By: Relevance
“…The design and methodology of the GCKD study has previously been reported in detail [24,25]. Briefly, the GCKD study is an ongoing prospective observational national cohort study including 5,217 Caucasian patients with CKD of moderate severity from a broad etiologic spectrum.…”
Section: German Chronic Kidney Disease Study (Gckd Study)mentioning
confidence: 99%
“…The design and methodology of the GCKD study has previously been reported in detail [24,25]. Briefly, the GCKD study is an ongoing prospective observational national cohort study including 5,217 Caucasian patients with CKD of moderate severity from a broad etiologic spectrum.…”
Section: German Chronic Kidney Disease Study (Gckd Study)mentioning
confidence: 99%
“…1844 subjects had diabetes and in 783 diabetic nephropathy is considered the leading cause of renal failure. The eGFR of diabetic patients in GCKD at baseline was 45 ml/min/1.73m 2 and the urinary albumin/creatinine ratio was 58 mg/g, their HbA1c level averaged 7% and 84% were on RAS blocking agents [10-12]. …”
Section: Discussionmentioning
confidence: 99%
“…Many SNPs that have been significantly associated with CKD are only nominally associated with ESRD if at all, perhaps suggesting different roles of action or the need for more carefully phenotyped cohorts. Large observational CKD studies such as GEnetics of Nephropathy: an International Effort (GENIE) [49], Chronic Renal Insufficiency Cohort (CRIC) [50] and German Chronic Kidney Disease Study (GCKD) [51] will allow more insight into the development of ESRD, and hopefully lead to the identification of a more comprehensive risk profile for both CKD and ESRD.…”
Section: Discussionmentioning
confidence: 99%